The barley (Hordeum vulgare) cellulose synthase‐like D2 gene (HvCslD2) mediates penetration resistance to host‐adapted and nonhost isolates of the powdery mildew fungus. Issue 2 (28th June 2016) - Douchkov, Dimitar; Lueck, Stefanie; Hensel, Goetz; Kumlehn, Jochen; Rajaraman, Jeyaraman; Johrde, Annika; Doblin, Monika S.; Beahan, Cherie T.; Kopischke, Michaela; Fuchs, René; Lipka, Volker; Niks, Rients E.; et al.
Summary: Cell walls and cellular turgor pressure shape and suspend the bodies of all vascular plants. In response to attack by fungal and oomycete pathogens, which usually breach their host's cell walls by mechanical force or by secreting lytic enzymes, plants often form local cell wall appositions (papillae) as an important first line of defence. The involvement of cell wall biosynthetic enzymes in the formation of these papillae is still poorly understood, especially in cereal crops. To investigate the role in plant defence of a candidate gene from barley ( Hordeum vulgare ) encoding cellulose synthase‐like D2 (HvCslD2), we generated transgenic barley plants in which HvCslD2 was silenced through RNA interference (RNAi). The transgenic plants showed no growth defects but their papillae were more successfully penetrated by host‐adapted, virulent as well as avirulent nonhost isolates of the powdery mildew fungus Blumeria graminis . Papilla penetration was associated with lower contents of cellulose in epidermal cell walls and increased digestion by fungal cell wall degrading enzymes. The results suggest that HvCslD2 ‐mediated cell wall changes in the epidermal layer represent an important defence reaction both for nonhost and for quantitative host resistance against nonadapted wheat and host‐adapted barley powdery mildew pathogens, respectively. Abstract : See also the Commentary on this article by Voigt, 212 : 303–305 .